Lower Internal Additive Noise and Better Perceptual Template Characterize Binocular Contrast Sensitivity Summation - Zhang, Pan; Wang, Hanlin; Ren, Weicong; Lu, Qing; Li, Chenxi; Chen, Ge; Zhang, Shilei; Tao, Jiayu; Li, Ying; Wu, Di; Wang, Zeng (Frontiers in Psychology, 2021)
Binocular summation is generally defined as the superiority of binocular over monocular performance. Here, we investigated how external noise modulates the effect of binocular summation on the contrast sensitivity function (CSF) and clarified the corresponding mechanisms by a perceptual template model (PTM). Contrast sensitivity (CS) over ten spatial frequencies and three external noise levels was assessed in one binocular and two monocular viewing conditions. Binocular summation ratio (BSR) was calculated by dividing the area under the log CSF (AULCSF) or CS of using both eyes by the that of only using ‘good eye’ (BSRG) or ‘bad eye’ (BSRB), respectively. We found that: (1) Based on the AULCSF, the BSRB was higher than BSRG. (2) Based on the AULCSF, the BSR was more pronounced in zero-noise than that in low-noise condition, but the BSR was not obvious higher than 1 in high-noise condition due to a large individual difference. (3) Based on the CS, with increasing spatial frequencies, the BSRB steadily increased. (4) Both decreased additive internal noise and improved perceptual template accounted for the binocular summation gain. These results help us better understand the features of binocular CS and shed light on the clinical studies of populations with monocular CS loss.